2022
DOI: 10.1029/2021jb022750
|View full text |Cite
|
Sign up to set email alerts
|

Source Properties of Hydraulic‐Fracturing‐Induced Earthquakes in the Kiskatinaw Area, British Columbia, Canada

Abstract: This work presents a high resolution source property study of hydraulic fracturing induced earthquakes in the Montney Formation, a low‐permeability tight shale reservoir in the Kiskatinaw area, northeast British Columbia, Canada. We estimate source parameters, including focal mechanism solutions (FMSs), seismic moment, spectral corner frequency, and static stress drop values of earthquakes recorded between July 2017 and July 2020. Waveform‐similarity‐based event classification of 8,283 earthquakes yields 52 ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 153 publications
(312 reference statements)
0
13
0
Order By: Relevance
“…(Published values in Kiskatinaw are based limited observations of ∼2 wells (Bell & Grasby, 2012; Heidbach et al., 2018; Shen et al., 2019)). A recent induced earthquake focal mechanism study in Kiskatinaw (Roth et al., 2022) found predominantly left‐lateral strike‐slip focal mechanisms with nodal planes at shallow angles to the regional SHmax, suggesting low spatial variability in SHmax in our study area. We note that SHmax is a parameter worth investigating in cases where observations exist at sufficient spatial resolution (e.g., from borehole measurements) near injection wells and/or seismicity.…”
Section: Discussionmentioning
confidence: 44%
“…(Published values in Kiskatinaw are based limited observations of ∼2 wells (Bell & Grasby, 2012; Heidbach et al., 2018; Shen et al., 2019)). A recent induced earthquake focal mechanism study in Kiskatinaw (Roth et al., 2022) found predominantly left‐lateral strike‐slip focal mechanisms with nodal planes at shallow angles to the regional SHmax, suggesting low spatial variability in SHmax in our study area. We note that SHmax is a parameter worth investigating in cases where observations exist at sufficient spatial resolution (e.g., from borehole measurements) near injection wells and/or seismicity.…”
Section: Discussionmentioning
confidence: 44%
“…Another possible case of active development of RSS is in the Dawson Creek area of British Columbia, ∼200 km NW of our study area (Figure 2). Although reliable moment‐tensor solutions for minor to moderate‐sized IIEs in this area are not available until 2017, due to the relatively poor station coverage in this part of Canada, earthquakes before 2014 seem to be purely thrust‐faulting (Kao et al., 2018), while during the more recent period of 2017–2020, the portion of thrust‐faulting ruptures dropped to only 22% (the remaining 78% are mostly strike‐slip events, Roth et al., 2022). The coexistence of different faulting types is also compatible with the limited number of rupture directivity observations in the region (Holmgren et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Applying Simpson's approach to the combined 103 compiled focal mechanisms revealed that a strike-slip fault system is the dominant tectonic regime in the area, with an average Anderson fault parameter of A ϕ ≈ 1.20 around Musreau Lake and A ϕ ≈ 1.7 around Fort St John. Of the 103 focal mechanisms, 93 are strike-slip faulting events and the remainder are large-magnitude reverse faulting events that occurred in the Fort St. John Graben system 7 in the northern part of the study area. Roth et al 7 states that there is no obvious relationship between the faulting style events and hypocentral depth.…”
Section: State Of Stress In the Montney Formationmentioning
confidence: 99%
“…Of the 103 focal mechanisms, 93 are strike-slip faulting events and the remainder are large-magnitude reverse faulting events that occurred in the Fort St. John Graben system 7 in the northern part of the study area. Roth et al 7 states that there is no obvious relationship between the faulting style events and hypocentral depth. Note that earthquake events recorded around Musreau Lake are not the result of injection operations in the Montney Formation but rather the result of injection at deeper depths in the Winterburn Formation 35 .…”
Section: State Of Stress In the Montney Formationmentioning
confidence: 99%